PENGARUH MODIFIKASI PERMAINAN FUTSAL TERHADAP MINAT BELAJAR SISWA DI SD KELAS IV BALEKAMBANG 01 - Tri Putra Jagat Satrio; Bayu Thomi Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of futsal game modification on the learning interest of fourth-grade students at SDN Balekambang 01. The background of this research stems from the low level of student interest in physical education (PJOK) lessons, often indicated by a lack of active participation and enthusiasm. To address this issue, a modified version of futsal—integrated with a “cat-and-mouse” game concept—was implemented to make the learning process more engaging and enjoyable for students.This research employed a quantitative approach with a quasi-experimental method, using a nonequivalent control group design. The sample consisted of 60 students, divided into two groups: the experimental class (IV A) and the control class (IV B), with 30 students in each. The instrument used was a learning interest questionnaire that had previously been validated and tested for reliability.The results revealed a significant difference in learning interest between the experimental and control classes. The average post-test score in the experimental class was 87, while the control class scored 83. The highest score in the experimental class was 97 and the lowest was 76, with a standard deviation of 6.128 and variance of 37.551. In contrast, the control class had a highest score of 93, a lowest score of 76, a standard deviation of 5.673, and a variance of 32.185. Normality and homogeneity tests confirmed that the data were normally distributed and homogeneous. The independent sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant effect of the futsal game modification on students’ learning interest.In conclusion, the implementation of a modified futsal game has a positive and significant impact on increasing the learning interest of fourth-grade students in PJOK classes.